2012
DOI: 10.1371/journal.pone.0044110
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid Treatment Ameliorates Acute Lung Injury Induced by 2009 Swine Origin Influenza A (H1N1) Virus in Mice

Abstract: BackgroundThe 2009 influenza pandemic affected people in almost all countries in the world, especially in younger age groups. During this time, the debate over whether to use corticosteroid treatment in severe influenza H1N1 infections patients resurfaced and was disputed by clinicians. There is an urgent need for a susceptible animal model of 2009 H1N1 infection that can be used to evaluate the pathogenesis and the therapeutic effect of corticosteroid treatment during infection.Methodology/Principal FindingsW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 30 publications
0
26
0
1
Order By: Relevance
“…The use of corticosteroids is based on the underlying pathogenesis of severe influenza infection, which is characterized by overproduction of proinflammatory cytokines/chemokines and an excess of activated lymphocytes, which may result in severe lung damage and delayed recovery . Moreover, animal model studies also found that corticosteroid treatment decreased mortality and ameliorated the acute lung injury induced by influenza A(H1N1)pdm09 virus . Although corticosteroids are posited to be beneficial in the treatment of severe influenza patients, clinical results remain contradictory and opposition overwhelms support in studies published so far .…”
Section: Introductionmentioning
confidence: 99%
“…The use of corticosteroids is based on the underlying pathogenesis of severe influenza infection, which is characterized by overproduction of proinflammatory cytokines/chemokines and an excess of activated lymphocytes, which may result in severe lung damage and delayed recovery . Moreover, animal model studies also found that corticosteroid treatment decreased mortality and ameliorated the acute lung injury induced by influenza A(H1N1)pdm09 virus . Although corticosteroids are posited to be beneficial in the treatment of severe influenza patients, clinical results remain contradictory and opposition overwhelms support in studies published so far .…”
Section: Introductionmentioning
confidence: 99%
“…Although corticosteroid was shown effective in treating mouse ALI induced by 2009 S-OIV H1N1 infection [12], modulation of the host immune response with less selective pressure on viral populations is enticing. MDX-1100, a fully human anti-IP-10 monoclonal antibody, is well tolerated and demonstrated clinical efficacy in patients with rheumatoid arthritis who responded inadequately to Methotrexate in a phase II, randomized, double-blind, placebo-controlled study [13].…”
mentioning
confidence: 99%
“…The use of glucocorticoids in the treatment of severe viral pneumonia has come from the experience of SARS treatment in Guangzhou, China. SARS coronavirus induces a IFN-γ-related cytokine storm in patients, which might be involved in the immunopathological damage observed in patients with SARS (81). A retrospective study of Guangzhou SARS cases showed that corticosteroid use reduced mortality and shortened hospitalization (82).…”
Section: Importance Of Anti-inflammatory Therapymentioning
confidence: 99%